The Eurasian Space in Chinese Official and Academic Discourses - I. E. Denisov; I. A. Safranchuk (Vestnik MGIMO-Universiteta, 2024)
The «Belе and Road Initiative» (BRI), proposed by China, marked a new phase in its external openness and growing desire to influence regional and global processes. However, BRI should not be viewed solely as a Chinese blueprint for restructuring Eurasia. The broad interpretative and geographical scope set by Chinese authorities allows flexibility in adapting the initiative to specific regions and countries, which is strategic for modifying or withdrawing commitments as needed. This paper examines why BRI has not become the foundation for a Chinese concept of Eurasia despite its significant impact on regional geopolitics.Our analysis begins with a critical examination of President Xi Jinping's speech at Nazarbayev University in 2013, identifying the nuanced usage of «Eurasia» that primarily refers to the post-Soviet space rather than the entire Eurasian continent. We delve into the subsequent official documents, noting the delay and ambiguity in defining the geographical and conceptual boundaries of BRI. The 2015 document, "Vision and Actions on Jointly Building Silk Road Economic Belt and 21st-Century Maritime Silk Road," illustrates the initiative's extensive and vague geographical scope, indicating that China did not initially aim for a broad Eurasian strategy.By employing Critical Discourse Analysis (CDA), we uncover how China's official rhetoric strategically frames BRI. The analysis reveals that Chinese discourse emphasizes bilateral rather than multilateral engagements within Eurasia, reflecting a «point-to-point» rather than a networked approach. This strategic ambiguity allows China to navigate its relationships with key regional players, notably Russia and the Central Asian states, without committing to a comprehensive Eurasian integration framework.The findings highlight the cautious and adaptive nature of China's engagement with Eurasia. The shift from a regional to a global scope in BRI discourse underscores China's pragmatic approach in balancing its regional ambitions with global aspirations.